2005
DOI: 10.3341/kjo.2005.19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Basic Fibroblast Growth Factor on Fibrovascular Ingrowth into Porous Polyethylene Anophthalmic Socket Implants

Abstract: To investigate the effect of basic Fibroblast Growth Factor (bFGF) on fibrovascular ingrowth into porous polyethylene orbital implants (Medpor) and to investigate any differences according to the method of administration. For the treated groups, after evisceration and Medpor implantation, bFGF was administered by soaking Medpor in the bFGF solution, and/or by injecting bFGF into the Medpor 1 week after the operation. Implants were removed 4 weeks after the operation and examined for the degrees of fibrovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Many studies have demonstrated that fibrovascular tissue ingrowth ocuurs from adjacent tissue into the porous PE from the periphery area toward the center of the implant. [9][10][11] However, the ophthalmologists find that PE implants are hard to suture and sometimes causes the suture needle to bend. Full impregnation of antibiotic solution into the implants, which is generally done to prevent infection, also takes a long time to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that fibrovascular tissue ingrowth ocuurs from adjacent tissue into the porous PE from the periphery area toward the center of the implant. [9][10][11] However, the ophthalmologists find that PE implants are hard to suture and sometimes causes the suture needle to bend. Full impregnation of antibiotic solution into the implants, which is generally done to prevent infection, also takes a long time to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al concluded that bFGF soaked or injected PP implants have low risk of implant exposure from delayed biointegration. 31 Wound healing is a complex process and many different types of growth hormones play a role in different phases of it. 32,33 A single type of growth hormones may play a positive role in the biointegration of PP, but fibrovascularization needs more than 1 growth hormone and cellular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known as a potential mediator of intraocular angiogenesis. Park et al [26] reported that the fibrovascular ingrowth rate is higher in bFGF-treated porous polyethylene implants. In this study, bFGF staining was performed to identify the implant that yielded the strongest bFGF expression.…”
Section: Discussionmentioning
confidence: 99%